PROMOTIONAL PRACTICES WITH GIVEAWAY AS ATTRACTION OF CONSUMER INTEREST IN ISLAMIC ECONOMIC PERSPECTIVE (CASE STUDY OF ISTAGRAM ACCOUNT @FATIM_KIDS15) - Rizki Syahputra; Sutoyo Sutoyo; Emalia Ariska (Jurnal Ekonomi, 2022)
Previously trading was done manually, now it is done online via e-commerce. Many conveniences and has a lot of influence for the development and progress of a business. The development of a promotional business is one of the ways that a producer or business actor does to attract consumers and users of goods to be able to get them. By definition, promotion is an act carried out by producers to get income. Current technological advances, especially the advancement of the internet, have many market places available for online transactions. The promotion method with Instagram is now an option for businesses. The current promotional trend is a conditional giveaway or prize, which is a gift given free of charge without spending money, however, there are terms and conditions that must be obeyed to get the prize. There are two problems examined in this research, namely; (1) What are the driving factors for business actors to hold promotions with giveaways. (2) How is the Islamic Law Review of promotional practices with giveaways as an attraction for consumer interest on the fatim_kids15 Instagram account. The type of research used and this research is field research, namely where research activities use data obtained from field observation activities. With primary data obtained from interviews, documentation, and secondary data obtained from journals, books on fiqh muamalah.